The Making of a Mobile Society in Modern Guangdong and the Protestant Churches’ Response - XUE, Ximing (Journal of Research for Christianity in China (JRCC), 2025)
Modern Guangdong society was characterized by high mobility, shaped by the development of modern transportation, the emergence of overseas Cantonese hometowns, and large-scale outward migration. In response to this dynamic context, Protestant churches in Guangdong strategically adapted their missionary routes, launched gospel watercraft to serve mobile populations such as the Dan people, established indigenous self-governing churches in the hometown of overseas Cantonese, and fostered Christian practices through faith networks that connected migrants with local believers. While this mobility posed significant challenges—such as the expansion of parish boundaries, the dispersion of congregants, and the destabilization of church communities resulting from extensive migration—Protestant churches in Guangdong responded proactively. Their adaptive strategies were manifested in three major transitions: from church planting to broader missionary outreach, from localized congregations to cross-regional missionary networks, and from ethnically defined churches to more inclusive, cross-cultural faith communities.